2018
DOI: 10.18632/oncotarget.24267
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib significantly enhances in vitro apoptosis in Hodgkin lymphoma and primary mediastinal B-cell lymphoma and survival in a lymphoma xenograft murine model

Abstract: Hodgkin lymphoma (HL) and primary mediastinal B-cell lymphoma (PMBL) share similar molecular features by gene expression profiling. Frequent gains of chromosome 9p exhibit higher Janus Kinase 2 (JAK2) transcript levels with increased JAK2 activity, suggesting aberrant activity of JAK2 and STAT pathways. This signaling pathway alteration may in part play an important role in the pathogenesis and/or chemoradiotherapy resistance in HL and PMBL. Ruxolitinib is a potent and selective JAK1/JAK2 inhibitor, with activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 53 publications
(62 reference statements)
8
13
1
Order By: Relevance
“…CAM, chorioallantoic membrane; VEGF, vascular endothelial growth factor; sqPCR, semi-quantitative polymerase chain reaction; TAMR, tamoxifen resistant. improve survival in HL and PMBL xenograft mice (47). In the current study, we showed for the first time that STAT3 activity was highly increased in TAMR-MCF-7 cells, and that ruxolitinib inhibited cell proliferation and tumor growth in TAM-resistant breast cancer cells, though the inhibition intensity is marginal.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…CAM, chorioallantoic membrane; VEGF, vascular endothelial growth factor; sqPCR, semi-quantitative polymerase chain reaction; TAMR, tamoxifen resistant. improve survival in HL and PMBL xenograft mice (47). In the current study, we showed for the first time that STAT3 activity was highly increased in TAMR-MCF-7 cells, and that ruxolitinib inhibited cell proliferation and tumor growth in TAM-resistant breast cancer cells, though the inhibition intensity is marginal.…”
Section: Discussionsupporting
confidence: 47%
“…Among these, tofacitinib (Xeljanz) and ruxolitinib have been approved for the treatment of rheumatoid arthritis, myelofibrosis, and polycythemia vera (PCV), and are now in clinical trials for novel therapeutic applications, such as colitis and various solid tumors (pancreatic cancer, breast cancer, and non-small-cell lung cancer (NSCLC) (45). It has been reported that ruxolitinib suppresses Hodgkin's lymphoma (HL) and primary mediastinal B-cell lymphoma (PMBL) growth in vitro, and increases programmed cell death against lymphoma cells (47). Ruxolitinib has also been shown to significantly inhibit tumor growth and The control CAM of a 10-day-old chick embryo was exposed to PBS.…”
Section: Discussionmentioning
confidence: 99%
“…amplification [14]. The anti-tumor effect of ruxolitinib was also demonstrated in both HL and PMBL cells and xenograft models [15]. Although this discrepancy of previous pre-clinical studies with the results of our study could not be clearly explained, the influence of JAK2 signaling on the growth of tumor cells in human might be different from in vitro and in vivo models, and this might be related with different outcome of ruxolitinib in HL and PMBCL of this pilot study.…”
Section: Discussioncontrasting
confidence: 74%
“…Ruxolitinib significantly enhanced apoptosis in HL and PMBCL in vitro and promoted survival in a lymphoma xenograft murine model. 244 A phase 2 study (NCT01877005) of ruxolitinib in advanced relapsed or refractory HL showed poor efficacy as monotherapy (ORR 9.4% and CR 0%). 245 Ruxolitinib and navitoclax, a Bcl-2/Bcl-XL inhibitor, reduced the tumor burden and prolonged survival in an ATLL xenograft murine model.…”
Section: Jak-statmentioning
confidence: 99%